2019
DOI: 10.3390/ijms20246297
|View full text |Cite|
|
Sign up to set email alerts
|

Antibacterial, Antibiofilm, and Antiadhesive Properties of Different Quaternized Chitosan Derivatives

Abstract: In the era of antimicrobial resistance, the identification of new antimicrobials is a research priority at the global level. In this regard, the attention towards functional antimicrobial polymers, with biomedical/pharmaceutical grade, and exerting anti-infective properties has recently grown. The aim of this study was to evaluate the antibacterial, antibiofilm, and antiadhesive properties of a number of quaternized chitosan derivatives that have displayed significant muco-adhesive properties and wound healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…They are soluble in water and have proved high antimicrobial and antibiofilm activity depending on the number of cationic groups [54,[56][57][58] and can be eligible for application in pharmaceutic and biomedical fields as agents against infection by implantation of medical devices.…”
Section: Chitosanmentioning
confidence: 99%
“…They are soluble in water and have proved high antimicrobial and antibiofilm activity depending on the number of cationic groups [54,[56][57][58] and can be eligible for application in pharmaceutic and biomedical fields as agents against infection by implantation of medical devices.…”
Section: Chitosanmentioning
confidence: 99%
“…In a previous study we demonstrated that a quaternary Chitosan-derivative (QAL)—characterized by low molecular weight, high degree of substitution (over 80%), and short chains containing two adjacent quaternary ammonium groups—possesses antibacterial, antibiofilm, and antiadhesive properties against Staphylococcus epidermidis and P. aeruginosa . [ 18 ]. The same derivative also demonstrated mucus-adhesive capability as well as wound-healing promotion, suggesting its possible use as a therapeutic agent in bacterial infections [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of N + -rCh-CD MW was carried out by determining the variation of the scattering intensity [ 19 ]. For this purpose, an aqueous (Milli-Q) N + -rCh-CD stock solution (3 mg/mL) was prepared and used to obtain samples in the 0.15–1.50 mg/mL concentration range.…”
Section: Methodsmentioning
confidence: 99%